Pengaruh Lingkungan Kerja dan Keselamatan Kesehatan Kerja Terhadap Kinerja Karyawan CV. Meera Jaya Sentosa Kota Tasikmalaya - Dela Setia Padiani Haya; Suci Putri Lestari; Ai Kusmiati Asyiah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This purpose of this study to determine the effect of work environment and occupational health safety on employee performance CV. Meera Jaya Sentosa Kota Tasikmalaya. The method used is a quantitative method with a research sample of 50 respondents who are an employee at CV. Meera Jaya Sentosa at Kota Tasikmalaya. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously work environment and occupational health safety has a significant influence on employee performance. Partially work environment has a significant influence on employee performance. Partially occupational health safety has a significant on employee performance.